La invasión turca y sus efectos sobre la población y el legado cultural de la Isla - Zorbas D., Alejandro; Nikolaidis, Nikiforos (Byzantion Nea Hellás, 2015)
In order to study this tapie, the authors examine the historie record ofthe Greek and Turkish population in Cyprus. The first one had been settledthere from the year 1.500 BC, while the Turkish inhabitants arrived 3.000years later, in 1571. According to the 1973 census, the 78,91% of the totalpopulation was Greek, being the Turkish only the 18,36%.As a consequence of the 1974 Turkish invasion, 200.000 Greek people were expelled from their lands and bornes, Besides, the Turkish set out to the task of re-populating the region with settlers from Anatholia. From the20.000 Greek people who managed to stay in their bornes in 1974, only 487were still there in 1997.Parallel to this process of forced change in the island's demography,one of the deepest and most visible result of the Turkish invasion has been thecultural transformation of the occupied territory into a Turkish province.The authors explain in detail the profanation and sacking of the cultural heritage in the occupied areas. Perhaps the best example of the natureof the invasion is the sacking of North Cyprus. The authors show concretedata about masterpieces of art - mainly religious - which have been stolen,sold, lost or destroyed, This systematic process of destruction is one of theworst disasters of our time.